The role of maritime safety in strengthening the marine ship management ((An exploratory study in the General Company for Maritime Transport)): The role of maritime safety in strengthening the marine ship management ((An exploratory study in the General Company for Maritime Transport)) - Ashour, Ali (The Gulf Economist, 2023)
The research aims to enhance the level of maritime safety in the Iraqi marine vessels belonging to the General Company for Maritime Transport, which is reflected in improving the efficiency of the work of marine vessels and increasing their operational efficiency. In order to achieve the objectives of the research, the researcher built a Theoretical Framework that shows the nature of the relationship between the main variables represented in the independent variable (maritime safety) and the dependent variable (marine ship management), where the Population of study was (390) individuals and the sample size (194) individuals, and the questionnaire form was distributed to the sample, represented by individuals working in marine vessels belonging to the General Company for Maritime Transport, the researcher used statistical programs to analyze data (EXCEL V.10, SPSS. V.23). The results of the research reached the acceptance of the main hypothesis, which aims to link and influence between the independent variable (maritime safety) and the dependent variable (marine ship management) as well as to clarify the weaknesses that threaten the safety of Iraqi naval vessels belonging to the State Company for Maritime Transport.